Impact of Endurance Testing on the Thermal Performance of a Retrofitted FDM 3D Printer - Alexander Ariantono Nugroho; David Christanto; Laurentius Yudha Bramantyo; Bondan Wiratmoko Budi Santoso; Ign. R. Haryosuprobo; Mardiatno (Jurnal Rekayasa Mesin, 2026)
The reliability of retrofitted Fused Deposition Modeling (FDM) 3D printers is affected by thermal stability during long print cycles. This study evaluated the thermal performance of a retrofitted BFB 3D Touch Cartesian FDM printer equipped with dual extruders, automatic bed leveling, a BTT SKR v1.4 controller, and a 24 V/360 W power supply unit (PSU). An 80 × 80 × 80 mm calibration cube was printed for 5 h to impose a continuous thermal load. Surface temperatures of stepper drivers, stepper motors, mainboard, PSU, and heated bed were measured with a TR-10 thermal imager at 1 h intervals, while bed preheating was recorded for 7 min at P1-P4 and the bed center. The Y1 driver reached 68.7 °C at hour 3, the PSU reached 65.0 °C at hour 5, and the extruder motor reached 52.7 °C. The bed center reached 59.2 °C at minute 7, but the corner regions were lower and locally non-monotonic. These fluctuations are interpreted as effects of local heat-transfer non-uniformity and measurement instability rather than uniform bed cooling. This study shows that driver and PSU cooling, cable-size verification, repeated measurements, and bed insulation are required to improve retrofit-printer reliability in extended operation.